Continuous-flow hydration–condensation reaction: Synthesis of α,β-unsaturated ketones from alkynes and aldehydes by using a heterogeneous solid acid catalyst - Rueping, Magnus; Bootwicha, Teerawut; Baars, Hannah; Sugiono, Erli (Beilstein Journal of Organic Chemistry, 2011)
A simple, practical and efficient continuous-flow hydration–condensation protocol was developed for the synthesis of α,β-unsaturated ketones starting from alkynes and aldehydes by employing a heterogeneous catalyst in a flow microwave. The procedure presents a straightforward and convenient access to valuable differently substituted chalcones and can be applied on multigram scale.
Keywords: chalcones; flow reactor; green chemistry; heterogeneous catalysis, microwave